LANGUAGE ERRORS IN THE PRACTICE OF SPEAKING INDONESIAN LANGUAGE FOR INTERNATIONAL SCHOOL STUDENTS - Emelia Rosari Siregar; Rahmadsyah Rangkuti (Hikari: Jurnal Bahasa dan Kebudayaan, 2022)
This journal aims to find out the language errors in the practice of speaking Indonesian language for the International School students in Chandra Kumala School. It is known that the low students' learning motivation in Indonesian language in a school with an international curriculum. This case study research was carried out in the Covid-19 pandemic situation, and the data collection techniques used an in-depth-interview, observation, and note taking. The results show that (1) language errors in speaking can be classified into 4 types, pronunciation errors, intonation errors, sentence errors, fluency and pauses; (2) the language errors were caused by 5 factors, i.e nervosity, mastery of topics, lack of vocabularies, diction, and grammatical mastery. The students who are mostly Indonesian citizens are expected to know and fluent to speak Indonesian language. But it does not happen in the International School. The impact of this phenomenon is that students do not have a psychological attachment to the Indonesian language. If this is allowed, students will grow up to become Indonesian citizens who are ignorant of their own language.